The use of Multithreshold Cross Sections for the Image Analysis of the Microstructure Surface - I.N. Kolupaev; V.O. Sobol’ (Журнал нано- та електронної фізики)
The problems of computer materials of complex surfaces and ways of solving them were discussed. For processes – pickling steel with non-metallic inclusions, condensation vacuum arc coating droplet phase, as well as magnetron sputtering under non-equilibrium conditions strongly strained surfaces of solid solutions quasi binary boride systems, the relations between the characteristics of the surface structure and its fractal dimension were established.